Annual Plan 1995-96 Volume-VI XII. General Services General Areas Government of Assam - Planning Commission (Planning Commission, 1995)
The Health plan proposals aim at providing curative, preventive, maternity and child heal the, nutrition and family welfare services. the plan proposals also aim at giving adequate medical coverage in Tribal and backward areas. Keeping in view of above points the plan proposals for 1995—96 have been formulated.
Government of Assam, Planning and Development Department